Unusual case of congenital/infantile fibrosarcoma in a new born - Eddiba Tarik; Rouas lamiae; Amrani Abdelouahed; Madhi Tarik; Gourinda Hassan; Dendane Mohammed Anouar (Wolters Kluwer Medknow Publications, 2013)
Congenital infantile fibrosarcoma (CIFS) is a rare mesenchymal tumor that is primarily developed in the soft tissue of distal extremities and occasionally in unusual locations such as the lung and retroperitoneum. It occurs mainly in children below the age of 5 years. About 200 cases have been reported in the literature so far, very few of them in new-borns. The prognosis of this tumor is relatively good compared to adult forms. We report an unusual case of CIFS occurring in new-born mimicking an hemangioma and causing hemorrhage in the neonatal period. The tumor is located in the left arm and axilla and associated with a hand malformation. A shoulder amputation is performed after chemotherapy failure. The infant is now two-years old with no recurrence.